Analisa Model Penerapan Early Release untuk Mereduksi Banjir di Bendungan Raknamo - Meo, Maria Magdalena Moi; Seran, Sri Santi L. M. F.; Bees, Azarya (Local Engineering, 2026)
Raknamo Dam is a dam that has a storage capacity of 14.091 million/m3 of water with the aim of providing raw water, providing irrigation, developing tourism, freshwater fisheries and freshwater conservation, flood control and hydroelectric power generation (PLTA). This study aims to analyze how much elevation of water level drop and the amount of discharge that comes out (outflow) when flooding occurs if the early release model is applied as a flood controller with a scheme of utilizing the use of water pumps. From the results of the analysis with the early release scheme as a flood controller, the scenario used is the utilization of the use of water pumps for 5 days, 3 hours with a total of 4 submersible pumps calculated, each with a capacity of 6 m3/sec, so that it can reduce flooding in the 1000-year return period with a scheme of 1 pump unit with a discharge of 378.60 m3/sec from an elevation of +107.2 m to 106.9 m; scheme of 2 pump units with a discharge of 288.60 m3/s from elevation +107.2 m to +106.4 m; scheme of 3 pump units with a discharge of 198.60 m3/s from elevation +107.2 m to +105.9 m and scheme of 4 pump units with a discharge of 108.60 m3/s from elevation +107.2 m to +105.3 m.